Digital Transformation in Religious Education: Development of Interactive Application-Based Modules to Improve the Competence of Junior High School Teachers in Merauke, Indonesia - Pranyoto, Yohanes Hendro; Berangka, Dedimus (Journal of Community Service and Society Empowerment, 2025)
The rapid development of information and communication technology demands adaptation of learning methods, especially for Generation Z and Alpha students who are highly familiar with digital technology. However, many teachers still rely on conventional learning tools that are less engaging for students. This community service activity aimed to improve the competency of Catholic Religious Education teachers at the junior high school level in Merauke City in developing interactive digital teaching modules. The activity used participatory workshop methods involving 18 Catholic Religious Education teachers from various junior high schools in Merauke Regency. The workshop was conducted in three sessions: understanding the concept of interactive digital teaching modules, training in the use of educational applications, and presentation with evaluation and reflection. Data collection used pre- and post-activity assessments, observation, and documentation studies. Results showed significant improvement in teacher competency from an initial average score of 2.00 (sufficient category) to 3.45 (good category) after the workshop. All competency aspects experienced improvement, with the highest increase in AI-assisted teaching module development skills from 2.17 to 3.67. This activity successfully equipped teachers with knowledge and skills to develop interactive digital teaching modules that support more creative, engaging, and meaningful Catholic Religious Education learning.